The green bus and the viapolitics of intra-state deportations in Syria. - Hassouneh, Nadine (Journal of Ethnic & Migration Studies, 2023)
Scholarship on conflict-induced displacement predominantly focuses on movement that entails crossing state borders from the so-called south to the so-called north. This paper addresses internal displacement within Syria placing the displacement vehicle, the Green Bus, at the core of the inquiry. It probes a form of internal displacement that occurs following the cessation of openly violent conflict through 'reconciliations' reached between main conflict stakeholders. The paper investigates the busing of hundreds of thousands of Syrians from the until then opposition-held territories to the northwest of the country between 2014 and 2018 in what resembles deportations, albeit intra-state. Based on the author's work in the humanitarian response to the Syrian crisis between 2016 and 2019, followed with academic research on internal displacement, this paper illustrates the bus as a site of power, contestation, and resistance to the bussed and the bussers. It also demonstrates the complexities and [via]variations of moving people in a complex and heterogenous conflict setting. The paper contributes to debates on internal displacement, viapolitics, and intra-state deportation via centering the experience of busing in its linguistic context and referring to the abundant displaced-produced knowledge shared on various online outlets.